APPLICATION OF E-LEARNING ROLE PLAY FOR SUPLLY CHAIN MANAGEMENT IN REMOTE AREA SALES FORCE TO IMPROVE DISTRIBUTION PERFORMANCE - Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Moch Irwan Hermanto, Moch Irwan Hermanto; Abdussalam, Abdussalam; Guntur Jakariya, Guntur Jakariya; Musyfiq Amrullah, Musyfiq Amrullah; Ganis Sanhaji, Ganis Sanhaji; Riko Darma Putra, Riko Darma Putra (Media Nusantara, 2023)
PT HMS is a distribution company that distributes FMCG (Fast Moving Consumer Good) products. This distribution company is determined to distribute its products from the manufacturer/factory to the hands of consumers in a fresh condition, suitable for consumption, at prices according to recommendations and easily accessible to consumers. The distribution of FMCG products is carried out by the sales distribution system from warehousing to retail. From retail then distributed to consumers. Improving the distribution system, especially improving and developing the distribution system, including control and developing sales competence in the field, is very necessary to achieve the company's targets, namely Sales Volume and distribution. E-learning role-play simulations for supply chain management (SCM) can be highly effective in training and development contexts. Here's how role-play simulations can be utilized in e-learning for SCM: Supplier Negotiations, Demand Forecasting and Planning, Inventory Management, Logistics and Distribution. Risk Management. Collaborative Planning, Forecasting, and Replenishment (CPFR). Ethical and Sustainable Supply Chain Practices: Incorporate role-play scenarios that address ethical dilemmas and sustainable practices in SCM. Learners can explore issues like fair labor practices, environmental impact, and ethical sourcing decisions. Benefits of using e-learning role-play simulations for SCM include: Experiential Learning, Enhanced Engagement, Skill Development, Realistic Context When designing e-learning role-play simulations for SCM, it's essential to ensure scenarios are relevant, challenging, and aligned with learning objectives. Providing feedback and debriefing sessions after simulations can further enhance learning outcomes by reinforcing key concepts and encouraging reflection on decision-making processes